The Correlation between Family Characteristics and Husband and Wife Interaction during the Covid-19 Pandemic - Risda Rizkillah; Diah Krisnatuti; Tin Herawati (Journal of Family Sciences, 2021)
Pandemics not only can facilitate a special space for husband-wife and child relationships but also a significant stressor for most husbands and wives and children. This study aimed to analyze the relationship between family characteristics and husband-wife interactions during the Covid-19 pandemic. This study used a cross-sectional study design and conducted in June-November 2020. The respondent in this study was a wife from an intact family who has elementary school–senior high school-age children (SD-SMA). The number of respondents in this study was 452 respondents. Data collection in this study was carried out using google form. Based on the research result, the highest means of index owned by the love dimension and the smallest index owned by respect's dimension. There are significant differences between HEL wife and LEL wife in love dimension, respect dimensions, and a total of husband-wife interaction. The correlation test shows that there is a significant negative correlation between husband's age, wife's age, and the number of children with husband-wife interaction. Furthermore, the correlation test also shows that the husband's income positively correlates with husband-wife interaction. This study concludes that women's higher education and husband's high income can make husband and wife interaction better.